PENERAPAN METODE INKUIRI BERBANTUAN E-MODUL - Damarsasi, Dimas Gigih; -, Soeprodjo; -, Saptorini (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to determine the effect of the inquiry method assisted chemistry emodule toward the learning outcomes. Population in this study is XI-IA grader of Senior High School (SHS) student in Tegal for academic year 2011/2012. Determination of the sample with cluster random sampling system obtained two classes, both are XI-IA3 grader as a experimental group received treatment using the methods of inquiry method assisted chemistry e-module and XI-IA as a control group received treatment using conventional method assisted audio visual.The research data obtained by the method of documentation, tests, questionnaires, and observation. The results of the study showed that the experimental group had an average grade of 84.90 and a control group had an average grade of 74.03. Based on the analysis, the experimental group is better than the control group with t count (3.08)> t table (1.99). The conclusion of this research is the application of inquiry method assisted chemistry e-module effect on student learning outcomes on solubility and solubility product subject, which is indicated by the coefficient of correlation (rb) of 0.46 with the influence of 21, 61%Keyword: Inquiry Method, E-module Assisted